(untitled) (Culturas Científicas, 2024)
In this paper, I propose a possible anti-realist solution to the paradox of explanation. This proposal is in line with the instrumentalist position of Reiss (2012b, 2013) but goes further: a normative inferentialist position of explanation is proposed. First, I will show some fundamental aspects of inferentialism in the context of explanation, and then, I will show how an inferentialist position regarding paradox of explanation reduces to accepting the following three propositions: 1. models are true in the sense of true explanations, 2. models explain, and 3. only true explanations explain. This expresses a solution to the paradox insofar as it is perfectly possible to accept each of the three propositions.